Thermal bursting ionization for ambient mass spectrometry. Issue 3 (4th January 2016) - Pei, Jiying; Yu, Kefu; Wang, Yinghui
Abstract : Ambient ionization source, thermal bursting ionization (TBI), was characterized for complex liquid sample analysis with mass spectrometry. Abstract : Thermal bursting ionization (TBI), which was developed for organic reaction monitoring in our previous work, was investigated in detail for ambient mass spectrometry. The performance of TBI was validated by analysis of various compounds in both positive and negative modes. Besides, TBI is illustrated to be applicable to complex samples, such as fruit juice and skin-care products.